Pengaruh Literasi Keuangan dan Gaya Hidup Terhadap Pengelolaan Uang Saku Mahasiswa Universitas Negeri Padang - Yulia, Titi; Cerya, Efni (Jurnal Salingka Nagari, 2024)
This research purpose is to reveal the literacy of financial and lifestyle impact on the pocket money management of Universitas Negeri Padang students. This research type nclude in quantitative descriptive research. The study population were all Universitas Negeri Padang students in the 2017-2023 entry year, usingtechnique by proportional random sampling, which get the samples number using the formula of Slovin, then was got 100 samples. The data obtained through distributing questionnaires to students were processed and analyzed using analysis with descriptive, inductive analysis, multiple linear regression analysis, and test of hypothesis with support by SPSS 25: 1) Literacy of Financial has a significant effect on pocket money management, 2) Lifestyle has no effect on pocket money management, and 3) Literacy of financial and lifestyle have a simultaneous effect on pocket money management. The findings of this study indicate that the importance for literacy of financial and lifestyle in terms of pocket money management.